Comparative transcriptomic profiling of susceptible and resistant cultivars of pigeonpea demonstrates early molecular responses during Fusarium udum infection - Arnab Purohit (Nature Portfolio, 2021)
Abstract Vascular wilt caused by Fusarium udum Butler is the most important disease of pigeonpea throughout the world. F. udum isolate MTCC 2204 (M1) inoculated pigeonpea plants of susceptible (ICP 2376) and resistant (ICP 8863) cultivars were taken at invasion stage of pathogenesis process for transcriptomic profiling to understand defense signaling reactions that interplay at early stage of this plant–pathogen encounter. Differential transcriptomic profiles were generated through cDNA-AFLP from M1 inoculated resistant and susceptible pigeonpea root tissues. Twenty five percent of transcript derived fragments (TDFs) were found to be pathogen induced. Among them 73 TDFs were re-amplified and sequenced. Homology search of the TDFs in available databases and thorough study of scientific literature identified several pathways, which could play crucial role in defense responses of the F. udum inoculated resistant plants. Some of the defense responsive pathways identified to be active during this interaction are, jasmonic acid and salicylic acid mediated defense responses, cell wall remodeling, vascular development and pattering, abscisic acid mediated responses, effector triggered immunity, and reactive oxygen species mediated signaling. This study identified important wilt responsive regulatory pathways in pigeonpea which will be helpful for further exploration of these resistant components for pigeonpea improvement.